Determination of moisture content in lyophilized mannitol through intact glass vials using NIR micro-spectrometers - Cristian Rodrigo Muzzio; Nicolás Gabriel Dini; Laura Daniela Simionato (Universidade de São Paulo, 2011)
Determination of moisture content in lyophilized solids is fundamental to predict quality and stability of freeze-dried products, but conventional methods are time-consuming, invasive and destructive. The aim of this study was to develop and optimize a fast, inexpensive, noninvasive and nondestructive method for determination of moisture content in lyophilized mannitol, based on an NIR micro-spectrometer instead of a conventional NIR spectrometer. Measurements of lyophilized mannitol were performed through the bottom of rotating glass vials by means of a reflectance probe. The root mean standard error of prediction (RMSEP) and the correlation coefficient (R²pred), yielded by the pre-treatments and calibration method proposed, was 0.233% (w/w) and 0.994, respectively. A determinação do conteúdo de umidade em sólidos liofilizados é fundamental para se prever a qualidade e a estabilidade de produtos liofilizados, mas os métodos convencionais consomem muito tempo, são invasivos e destrutivos. O objetivo desse estudo foi desenvolver e otimizar um método rápido, econômico, não invasivo e não destrutivo para a determinação do conteúdo de umidade em manitol liofilizado, com base em microespectrômetro de infravermelho próximo ao invés de um espectrômetro de infravermelho próximo convencional. As medidas de manitol liofilizado foram realizadas através do fundo de recipiente de vidro em rotação por meio de sonda de reflectância. A raíz do erro médio padrão de predição (RMSEP) e o coeficiente de correlação (R²pred) obtidos pelo prétratamento e pelo método de calibração proposto foram, respectivamente, 0,233% (p/p) e 0,994.